A NOVEL NORMULINANE ISOLATED FROM Azorella compacta AND ASSESSMENT OF ITS ANTIBACTERIAL ACTIVITY - San-Martín, A.; Bacho, M.; Núñez, S.; Rovirosa, J.; Soler, A.; Blanc, V.; León, R.; Olea, A. F. (Journal of the Chilean Chemical Society, 2018)
Phytochemical analysis of Azorella compacta resulted in the isolation of six known diterpenes and one unknown norditerpene using chromatographic methods. The structure of this new compound was established by spectroscopic analysis. The bioactivity of the new compound was assessed against six oral bacteria using a drop test method. A high level of growth inhibition was observed against F. nucleatum and P. gingivalis; however, other species such as V. parvula and A. actinomycetemcomitans were not affected.